THE DEVELOPMENT AND QUALITY ASSURANCE OF EXERCISES OF BASIC VIOLIN SKILLS BASED ON IVAN GALAMIAN APPROACH - Suvattanavanich, Keera; Pumin, Prapansak (Fine Arts Journal: Srinakharinwirot University, 2021)
The purposes of this study are to develop the exercises of basic violin skills based on Ivan Galamian approach while maintaining the quality of the exercises at a satisfactory level and to investigate students’ satisfaction level of the exercises. The subjects of the study consist of violist experts who have made a contribution to music education and music performances in public and the high school students majoring in music with the specialization in violin of Satit Prasarnmit Demonstration School in the academic year 2020. The results of this study show that the violinist experts evaluated the quality of the exercises of basic violin skills based on Ivan Galamian approach at a satisfactory level ( = 4.28), and the level of students' satisfaction of the violin exercises is at a high level ( = 4.06). These results are aligned with the assumption of the study.